Isodon rubescens (Hemls.) Hara.: A Comprehensive Review on Traditional Uses, Phytochemistry, and Pharmacological Activities - Chen, Xufei; Dai, Xufen; Liu, Yinghai; He, Xirui; Gong, Gu (Frontiers in Pharmacology, 2022)
Isodon rubescens is a medicinal and food plant, often eaten as a wild vegetable in ancient China, and has been widely used for decades to treat sore throats, tonsillitis, colds and headaches, bronchitis, chronic hepatitis, joint rheumatism, snake and insect bites, and various cancers. This comprehensive and systematic review of the ethnomedicinal uses, phytochemical composition, pharmacological activity, quality control and toxicology of I. rubescens provides updated information for the further development and application in the fields of functional foods and new drugs research. To date, a total of 324 substances have been isolated and identified from the plant, including terpenoids, flavonoids, polyphenols, alkaloids, amino acids, and volatile oils. Among these substances, diterpenoids are the most important and abundant bioactive components. In the past decades pharmacological studies have shown that I. rubescens has significant biological activities, especially in the modulation of antitumor and multidrug resistance. However, most of these studies have been conducted in vitro. In-depth in vivo studies on the quality control of its crude extracts and active ingredients, as well as on metabolite identification are still very limited. Therefore, more well-designed preclinical and clinical studies are needed to confirm the reported therapeutic potential of I. rubescens.